The dissolution of Yugoslavia: a crossroads between East and West - Mindreau, Manuel (Universidad del Pacífico, 1993)
Invented by the Croats and put into practice by the Serbs, the “Yugoslav” ideal finally to be dying. A few decades of cohabitation were insufficient to bury the hatchet of an almost thousand year-old antagonism that this ill-fated union brought to the surface. Paradoxically, despite being much desired, it was precarious from the outset. Only the iron rule of communism held it together artificially. Today's war in Bosnia-Herzegovina, which has acquired religious implications with the resurgence of anti-islamic feeding in the Balkans, is the latest chapter in the history of the now twice defunct federation of “southern Slav states”.